Performans Ukuran Tubuh Umur 205 hari dan 365 hari Hasil Cross Breeding Induk Sapi Bali dengan Pejantan Sapi Brahman - Irwansyah Irwansyah; Junaedi Junaedi; Suparman Suparman; Khaeruddin khaeruddin (Faculty of Agriculture, Musamus University, 2021)
This study was conducted with the aim of knowing the performance of body size at the age of 205 days and 365 days of cross-breeding offspring from Bali cattle and Brahman bulls. This research was conducted from March to September 2021, which took place in Kolaka Regency, Southeast Sulawesi. The materials used were 50 cows that were artificially inseminated by Brahman bulls with Balinese cows. Parameters observed were body length (cm) aged 205 days and 365 days, chest circumference (cm) and shoulder height. The research results are; The body length of a cow aged 205 days was 96.04±2.4 cm and the body length of a cow aged 365 days was 106.28±1.82 cm, the chest circumference of a cow aged 205 was 125.78±2.94cm and a chest circumference of a cow aged 365 days was 143 ,78±4.09 cm, shoulder height of 205 days old cow 96.1±2.69 cm and shoulder height 105.74±2.17 cm. The conclusion is,, The performance of body measurements (body length, chest circumference, and shoulder height) cattle aged 205 days and 365 days from cross-breeding of Brahman bulls with Balinese mothers through artificial insemination programs is better than the marriage of Balinese bulls with cows. Bali. Crossing the Indicus (Brahman) cattle with the Sondaicus (Bali) cattle can improve the performance of the body size of the cattle.